Neuroprotective Effects of Fingolimod Supplement on the Retina and Optic Nerve in the Mouse Model of Experimental Autoimmune Encephalomyelitis - Yang, Tao; Zha, Zheng; Yang, Xiao; Kang, YueZhi; Wang, Xin; Tong, Yanping; Zhao, XueSong; Wang, Lei; Fan, YongPing (Frontiers in Neuroscience, 2021)
Favorable effects exerted by long-term administration of fingolimod therapy in multiple sclerosis (MS) patients have been reported, but sporadic side effects, such as reversible macular edema, also have been recorded. The present study aimed to determine whether fingolimod therapy is beneficial to the visual system in experimental autoimmune encephalomyelitis (EAE) mice. A decrease in demyelination and axon loss in the optic nerve as well as cellular infiltration, especially the recruited macrophages, was observed in EAE with fingolimod treatment. Fingolimod administration diminished hypergliosis of macroglia, including astrocytes and Müller cells in the retina and optic nerve in EAE. Microglia were hyperactivated in the retina and optic nerve in the EAE mice compared to controls, which could be alleviated by fingolimod treatment. Moreover, apoptosis of retinal ganglion cells (RGC) and oligodendrocytes in the optic nerve was significantly reduced with fingolimod treatment compared to that in the untreated EAE mice. These results suggested that fingolimod exerts neuroprotective and anti-inflammatory effects on the retina and optic nerve in a mouse model of EAE. Considering the paradox of favorable and side effects of fingolimod on visual system, we speculate that side effects including macular oedema caused by fingolimod during MS treatment is tendency to be vasogenic rather than hypergliosis in optic nerve and retina which warrants further neuroophthalmological investigation.